Feasibility Study of The Small and Medium-Sized Enterprises Fisheries Processing Unit and Their Mackerel Tuna Pindang Product in Banyuwangi - Dian Anggraeni; Nurjanah Nurjanah; Diah Asih Asmara; Taufik Hidayat (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Development of fisheries commodities to fulfill people needs could be achieved by creating of small and medium-sized enterprises (SMEs). This study was aimed to evaluate the feasibility of processing units and quality of mackerel tuna pindang product in a SME. The feasibility of the processing units was investigated through a survey and interview, while the product quality was determined based on the chemical composition, histamine and microbial test. The analyses showed that many deviations including 19 minor, 8 major, 28 serious and 22 critical deviations were occurred in the SME. These deviations suggest that the SME did not meet the regulation required by the government and was included in the Group D. Furthermore, the histamine and microbial levels indicate the product has been severely contaminated.